Thermophysical properties of castor oil (Ricinus communis l.) biodiesel and its blends - Gokdogan, Osman; Eryilmaz, Tanzer; Yesilyurt, Murat Kadir (CT&F - Ciencia, Tecnología y Futuro, 2015)
In this study, biodiesel (methyl ester) was produced from Castor Oil (Ricinus communis L.) (CO) using sodium hydroxide (NaOH) and methanol (CH3OH) by the two-step transesterification method. Nine different fuel blends (2, 5, 10, 20, 30, 40, 50, 60 and 75% by volume blending with diesel) were prepared. The density values of Castor Oil Biodiesel (COB) and its blends were measured at the temperature range from 0 to 93°C in steps of 5°C and the kinematic viscosity values of COB and its blends were measured at the temperature range from 30 to 100°C in the steps of 5°C. The results showed that the density, kinematic viscosity, calorific value, flash point, pH, copper strip corrosion and water content of COB are 932.40 kg.m-3, 15.069 mm2.s-1, 38.600 MJ.kg-1, 182°C, 7, 1a and 1067.7 mg.kg-1, respectively. The density and kinematic viscosity of fuel samples decrease as temperature increases; and also these properties decrease as a result of the increase in the amount of diesel in the blends.